Prediction and analysis of the glycemic consumptions of newborn's blood samples - Miguel Ángel Martos Monereo; Virginia López Martos (Fundación para el Desarrollo de la Enfermería, 2007)
Occasionally we can be with false situations of hypoglycemia in newborn caused by inadequate times of delay between extraction and analysis and therefore, it is necessary to make a new extraction and increase the baby controls. This is the reason why we proposed to elude these negative consequences elaborating the equation that calculates consumptions that occurs on any sample of unweaned babies in waiting times between 1 and 2 hours, and that will be by those variables that determine these consumptions.Observational, correlational and multivariant study, in which it is used blood samples of each unweaned baby admitted in the newborn unit, dividing them in three fractions to determinate hemogram, initial glucose, glucose after an hour of delay in the odds samples and glucose after two hours of delay in the even samples, writing down the age of the baby and the room temperature. N= 110Concluding, the glucolitic decrease in sanguineous samples of unweaned babies aged between 0 and 4 months, completely conserved and kept at room temperature between 1 and 2 hours, are related with the waiting time (p), number of red globules by unit of volume (h), and therefore with the haematocrit (ht), with the room temperature (t) and the age (e), responding the average glucolitic consumptions (CGM): 0.20 * ht, and the minimum glucolitic consumption (CGMi): CGMi: 0.34 * ht + 0.1 * p - 25, being this last the most suitable one for, when conflicting situations, discarding false hypoglycemia without a new extraction.